Analisis Kepuasan Pengguna Digilib Menggunakan Model EUCS di Smk Labor Pekanbaru - Nurmaini Dalimunthe; Febri Ramadhani Daulay (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
AbstractSMK Labor Pekanbaru having a digital library to support interest in reading students of SMK Labor Pekanbaru either manually or digitally that can be accessed quickly and easily via a computer network. But the problems that happens is the lack of response from the students to use this system. This study focused to determine the level of user satisfaction in using a Digital Library with a model approach End User Computing Satisfaction (EUCS), which consists of five factors: Content, Accuracy, Format, Ease Users, and timeliness as independent variables and user satisfaction as a variable dependent. The sample in this study amounted to 84 respondents. The sampling technique used in this research is Strata Random Sampling. Based on the partial results of the study showed that of the five independent variables studied, four variables were found to significantly affect the user's satisfaction variable is the variable content, accuracy, format, and timeliness. Ease variables not found to significantly affect user satisfaction variables. Then simultaneously can be seen that the variable content, accuracy, Format, Ease and timeliness together evident effect on the variable User Satisfaction. Adjusted R Square of 0.635 indicates that 63.5% User Satisfaction variables can be explained by the five independent variables. While the remaining 36.5% is explained by other factors. Keywords : digital library, EUCS, user satisfaction